The immunological pathogenesis of vitiligo and the potential role of mesenchymal stromal/stem cells in its treatment - Rui-Lin Yang; De-Zhi Zhao; Yi-Bing Yang; Han-Xiao Wei; Kang Yang; Yu-Jie Zhao; Wei-Hong Wan; Zu-Lin Liu; Yuan Feng; Qian Zhang; Tao Zhang (Journal of Translational Medicine)
Abstract Vitiligo is a dermatological condition that affects millions of individuals globally and is frequently precipitated by damage to or dysfunction of melanocytes. Despite the availability of various therapeutic options, the management of vitiligo remains a significant challenge, underscoring the necessity for innovative treatment approaches. Currently, Mesenchymal Stromal Cells (MSCs) have gained prominence as a therapeutic modality in the research of numerous diseases, owing to their remarkable paracrine effects, making them a promising strategy for immunomodulation and tissue repair. The downregulation of specific cytokines by MSCs has the potential to enhance the microenvironment of vitiligo lesions, thereby contributing to therapeutic outcomes. This article aims to review the immunologic pathogenesis of vitiligo, the involvement of certain cytokines in its pathogenesis, and the therapeutic potential of MSCs in the treatment of vitiligo. It is anticipated that this review will serve as a reference for future therapeutic strategies involving MSCs in the management of vitiligo.